Empowering the Muhammadiyah Kemasan Branch Community: Greening the Environment with Food Plants and Toga - Syah, Naufal Galfan; Santri, Erlina Widya; Dewi, Widya Kusuma; Abror, M (Universitas Muhammadiyah Sidoarjo, 2025)
Ranting Muhammadiyah Kemasan, in collaboration with KKNT-T students, focuses on community empowerment and environmental improvement at Masjid Al-Muhtadin. The main challenges are the lack of green space and poor waste management. The program consists of three stages: Observation, Implementation, and Maintenance. The observation stage identifies environmental issues such as disorganized construction materials and insufficient green areas. Implementation includes planting ornamental and TOGA plants and providing waste bins for organic and inorganic waste separation. Maintenance involves watering and educating the community on cleanliness. As a result, the aesthetics and comfort of the mosque environment have improved, TOGA plants offer long-term benefits, and community awareness of mosque cleanliness has increased, strengthening collective responsibility.